Silicon-based MEMS/NEMS empowered by graphene: a scheme for large tunability and functionality - Mengqi Fu; Zhan Shi; Bojan Bošnjak; Robert H. Blick; Elke Scheer; Fan Yang (Microsystems & Nanoengineering)
Abstract Integration of graphene in silicon-based micro-/nanoelectromechanical systems (MEMS/NEMS) marries the robustness of silicon-based materials with the exceptional physical properties of graphene, drastically enhancing the system’s regulation performance which now is key for many advanced applications in nanotechnology. Here, we experimentally demonstrate and theoretically analyze a powerful on-chip integration principle consisting of a hybrid graphene/silicon nitride membrane with metallic leads on top that enables an extremely large static and dynamic parameter regulation. When a static voltage is applied to the leads of the integrated structure, a spatially confined localized electrothermomechanical (ETM) effect results in ultra-wide frequency tuning, deformation (buckling transition) and regulation of the mechanical properties. Moreover, by injecting an alternating voltage to the leads, we can excite the resonator vibrating even far beyond its linear regime without a complex and space consuming actuation system. Our results prove that the scheme provides a compact integrated system possessing mechanical robustness, high controllability, and fast response. It not only expands the limit of the application range of MEMS/NEMS devices, but also enables the further miniaturization of the device. The graphene integrated MEMS/NEMS empowered by graphene: a scheme for strong enhancements of tunability and functionality of silicon based device device consists of a hybrid graphene/silicon-nitride membrane with metallic leads that enables ultra-wide frequency tuning, spatial deflection, mechanical properties tuning and on-surface actuation.